2022
DOI: 10.3390/ijerph19063271
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances, Degree of Disability and the Quality of Life in Multiple Sclerosis Patients

Abstract: Sleep disturbances are pervasive in patients with multiple sclerosis (MS), with incidence about four times higher compared to the general population. The most frequent primary sleep problems include insomnia, restless leg syndrome, sleep-related movement disorders, and sleep-disordered breathing. This study aims to assess the relationships between sleeping problems and the quality of life (QoL) in MS patients. This cross-sectional study was conducted among 152 MS patients (mean age: 36.27 ± 9.60) between Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
3
8
0
Order By: Relevance
“…To the best of our knowledge, this is the highest prevalence of poor sleep quality in PwMS observed to date. The most recent studies on the subject reported lower rates, with poor sleep quality observed in about half of the study participants [ 110 , 111 ] and insomnia in 66.45% [ 112 ]. Sleep is especially important in PwMS because of its role in brain regeneration and regulation of inflammatory processes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the highest prevalence of poor sleep quality in PwMS observed to date. The most recent studies on the subject reported lower rates, with poor sleep quality observed in about half of the study participants [ 110 , 111 ] and insomnia in 66.45% [ 112 ]. Sleep is especially important in PwMS because of its role in brain regeneration and regulation of inflammatory processes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, sleep quality appeared progressively worse with each of the disability subcategories ( p < 0.001, ω 2 = 0.125), and poor sleep quality was associated with depression, perceived stress, autonomy, and below-average income. These findings reveal a very significant burden on PwMS that often remains overlooked in MS care—sleep abnormalities are underdiagnosed in PwMS [ 30 ] despite their significant effects on one’s quality of life [ 112 ], and sleep assessment is not used in most MS care centers [ 27 ]. The elevated levels of poor sleep quality among Israeli PwMS may be related to the increased levels of stress in the Israeli society, yet a recent study that included 195,000 Israelis revealed an overall prevalence of sleep disorders—but not poor sleep quality specifically—that is similar to other Western countries [ 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent primary sleep disorders include sleep-disordered breathing, insomnia, RLS, and narcolepsy. 60 It is often difficult to differentiate MS-related fatigue (low energy) and excessive daytime sleepiness (falling asleep) associated with comorbid sleep disorders, which may contribute to secondary fatigue in people with MS (FIGURE 10-3). 61 Primary fatigue is related to the underlying demyelinating disease process, with possible pathophysiologic mechanisms including brain inflammation and structural changes, cytokine accumulation, autonomic dysfunction, and dysregulation of the hypothalamic-pituitary neuroendocrine pathways.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Sleep disorders are reportedly 4 times more prevalent in people with multiple sclerosis (MS) as compared with the general population. The most frequent primary sleep disorders include sleep-disordered breathing, insomnia, RLS, and narcolepsy 60 …”
Section: Multiple Sclerosismentioning
confidence: 99%
“…The prevalence and severity of sleep disturbances, including poor sleep quality, sleep fragmentation, sleep apnea, insomnia, and restless legs syndrome (RLS), are increased in PwMS 22-24 . Despite their high prevalence and impact, sleep disturbances often go unrecognized and untreated 25 , contributing to other symptoms as well as diminishing quality of life in PwMS 24,26,27 . Lastly, tobacco smoking is particularly harmful in the context of MS 28 .…”
Section: Introductionmentioning
confidence: 99%